Ethical considerations of population screening for late‐onset genetic disease. (15th March 2015) - Golden‐Grant, K.; Merritt, J.L.; Scott, C.R.
Abstract : Population‐based genetic screening has been a mainstay of public health in the United States for many years. The goal of genetic screening is to identify individuals at increased risk for treatable diseases. The evolution of genetic testing to include multi‐disease panels allows for new screening applications which challenge the traditional model of clinical genetics care by the identification of late‐onset disorders in an asymptomatic fetus, child, or adult. We present two unique examples of individuals referred to a biochemical genetics clinic due to the detection of late‐onset Pompe disease by population‐based screening modalities. We review early experiences in counseling and management of pre‐symptomatic individuals and highlight some of the primary ethical factors warranting consideration as we enter the era of genomic medicine.